Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/s005350070017
|View full text |Cite
|
Sign up to set email alerts
|

First line of defense: the role of the intestinal epithelium as an active component of the mucosal immune system

Abstract: of the monolayer. Intestinal epithelial cells can be defined as playing an important role in both innate and adaptive immune responses. This review attempts to outline some of the mechanisms by which IECs participate in both these forms of defense. Role of IECs in innate mucosal immunityThe intestinal lumen, particularly that of the colon, contains a large variety of bacteria and bacterially derived products. 1,2 A number of "broadly-specific" defense mechanisms have evolved to guard against the risk of attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 108 publications
0
71
0
2
Order By: Relevance
“…Data from previous studies have shown that differences occur in the immune functions of porcine epithelial cells and their interactions with other immune cell populations, compared with those from other species (Schierack et al, 2006). Epithelial cells play a pivotal role in coordinating host immune responses via production of several essential signalling molecules (such as cytokines and chemokines, as well as cell surface molecules), the expression of which is also regulated by NFkB (Moynagh, 2005;Pitman & Blumberg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Data from previous studies have shown that differences occur in the immune functions of porcine epithelial cells and their interactions with other immune cell populations, compared with those from other species (Schierack et al, 2006). Epithelial cells play a pivotal role in coordinating host immune responses via production of several essential signalling molecules (such as cytokines and chemokines, as well as cell surface molecules), the expression of which is also regulated by NFkB (Moynagh, 2005;Pitman & Blumberg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its function as a physical barrier, the intestinal epithelium influences local immune responses through expression of adhesion molecules, costimulatory factors, chemokines and cytokines [44]. Constitutive CCL20 expression in the intestine can be up-regulated by inflammatory stimuli [25,26,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, before antigens reach the GALT, antigens must breach the IEC monolayer that separates the GALT from the intestinal lumen. The IEC monolayer provides both intrinsic and extrinsic barriers to potentially harmful pathogens and antigens (reviewed by Pitman and Blumberg, 2000). The intrinsic mechanism hinges on the establishment of a physical barrier via the highly organized IEC monolayer, which facilitates selective transfer of lumenal contents to the underlying GALT.…”
Section: Galtmentioning
confidence: 99%